Clinical utility of cerebrospinal fluid biomarkers in the diagnosis of early Alzheimer’s disease - Blennow, Kaj (Alzheimers Dement, 2014)
Several potential disease-modifying drugs for Alzheimer’s disease (AD) have failed to show any effect on disease progression in clinical trials, conceivably because the AD subjects are already too advanced to derive clinical benefit from treatment and because diagnosis based on clinical criteria alone introduces a high misdiagnosis rate. Thus, well-validated biomarkers for early detection and accurate diagnosis are crucial. Low cerebrospinal fluid (CSF) concentrations of the amyloid-β (Aβ(1-42)) peptide, in combination with high total tau and phosphorylated tau, are sensitive and specific biomarkers highly predictive of progression to AD dementia in patients with mild cognitive impairment. However, interlaboratory variations in the results seen with currently available immunoassays are of concern. Recent worldwide standardization efforts and quality control programs include standard operating procedures for both preanalytical (e.g., lumbar puncture and sample handling) and analytical (e.g., preparation of calibration curve) procedures. Efforts are also ongoing to develop highly reproducible assays on fully automated instruments. These global standardization and harmonization measures will provide the basis for the generalized international application of CSF bio-markers for both clinical trials and routine clinical diagnosis of AD.